A conjugated polymer with high planarity and extended π-electron delocalization via a quinoid structure prepared by short synthetic steps. Issue 2 (5th December 2016) - Hwang, Hansu; Kim, Yunseul; Kang, Minji; Lee, Min-Hye; Heo, Youn-Jung; Kim, Dong-Yu
Abstract : A quinoidal polymer, PQuBTV, with high planarity and extended π-electron delocalization was synthesized by short synthetic steps. The polymerPQuBTV showed balanced ambipolar and high charge carrier mobilities. Abstract : An attractive synthetic strategy for incorporating a quinoidal molecule into a conjugated polymer backbone with three short steps is reported here. The quinoidal polymer, PQuBTV, exhibited high planarity and extended conjugation. As a result, ambipolar charge carrier mobilities of 0.52 cm 2 V −1 s −1 for holes and 0.53 cm 2 V −1 s −1 for electrons were observed in field-effect transistor devices.